2012
DOI: 10.1080/10888438.2011.601434
|View full text |Cite
|
Sign up to set email alerts
|

Peter Effect in the Preparation of Reading Teachers

Abstract: The Peter Effect (Applegate & Applegate, 2004) claimed that one cannot be expected to give what one does not possess. We applied this notion to reading teacher preparation and hypothesized that teacher educators who do not possess an understanding of basic language constructs would not prepare teacher candidates with an understanding of these constructs considered essential for early reading success. Results from a survey of basic language constructs revealed similar patterns in performance between teacher edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 16 publications
7
81
1
4
Order By: Relevance
“…The analysis also showed that there is much common variance shared by knowledge related variables (KPA, KFVC and KASSI) in the prediction of global perceived knowledge, and that there are suppression effects between variables. Although these results are similar to those found by others (e.g., Binks-Cantrell et al, 2012;Washburn et al, 2011), the large overlap between KPA, KFVC and KASSI, suggests that these variables represent one single factor. It seems therefore meaningless to explain the predictive value of any specific knowledge variables.…”
Section: Discussionsupporting
confidence: 33%
See 1 more Smart Citation
“…The analysis also showed that there is much common variance shared by knowledge related variables (KPA, KFVC and KASSI) in the prediction of global perceived knowledge, and that there are suppression effects between variables. Although these results are similar to those found by others (e.g., Binks-Cantrell et al, 2012;Washburn et al, 2011), the large overlap between KPA, KFVC and KASSI, suggests that these variables represent one single factor. It seems therefore meaningless to explain the predictive value of any specific knowledge variables.…”
Section: Discussionsupporting
confidence: 33%
“…In one of the most important studies about elementary teachers' education schools in the USA, Walsh et al (2006) concluded that "most education schools are not teaching the science of reading" (p. 22), that "much of current reading instruction is incompatible with science" (p. 29), and that "teacher educators portray the science of reading instruction as an approach that is no more valid than others" (p. 30). If undergraduate teachers are not receiving appropriate instruction, one can hardly expect them to be able to calibrate their perceived knowledge with the needed disciplinary knowledge (Applegate & Applegate, 2004;Binks-Cantrell, Washburn, Joshi, & Hougen, 2012).…”
Section: Revista Dementioning
confidence: 99%
“…La primera de ellas, la más abundante, ha mostrado consistentemente que los maestros, tanto estudiantes a punto de finalizar sus estudios como los maestros con experiencia profesional, tienen lagunas de conocimientos significativas acerca de los diferentes constructos lingüísticos (p.e. fonología, fonética, sintaxis y morfología) que están en la base de la enseñanza de la lectura en niños con y sin dificultades de aprendizaje (Binks-Cantrell, Joshi, Washburn y Hougen, 2012;Bos, Mather, Dickson, Podhajski y Chard, 2001;Chesman, McGuire, Shankweiler y Coyne, 2009;Joshi, Binks, Hougen, Dahlgren, Dean et al, 2009;Moats, 2009;Lopes, Spear-Swerling, Oliveira, Velasquez y Zibulsky, 2014;Moats y Foorman, 2003;Piasta, Connor McDonald, Fishman y Morrison, 2009;Spear-Swerling, 2007;Spear-Swerling, Brucker y Alfano, 2005;Washburn, Joshi y Binks-Cantrell, 2011a;Washburn, Joshi y Binks-Cantrell, 2011b). Obviamente, sin estos conocimientos los profesores no pueden proporcionar una instrucción a los niños que mejore sus habilidades lectoras, especialmente en los niños con dificultades de aprendizaje.…”
Section: Introductionunclassified
“…Failure to provide essential knowledge in science and exposure to its literature continues to promulgate ignorance with regard to educational knowledge, which is particularly the case with regard to reading, reading acquisition and reading failure. Binks-Cantrell et al, [82] refer to this lack of knowledge as the Peter Effect [83] in which individuals cannot teach what they do not know themselves. There is no specialization area that would lead to a doctorate in education that could forgo the Science of Reading content.…”
Section: Doctoral Trainingmentioning
confidence: 99%